Multiple squamous cell carcinomas in Congolese albino child. - Sferrazzo, F. (European Journal of Pediatric Dermatology, 2020)
Oculocutaneous albinism (OCA) is an inherited disease transmitted by an autosomal recessive trait and characterized by a normal number of melanocytes, which are not, however, able to synthesize melanin. This defect in white living in a temperate climate is less severe than in black living in an equatorial climate; in the latter the incidence of squamous cell carcinoma (SCC) is 1000 times higher. As in xeroderma pigmentosum, also in OCA the incidence of melanoma is much lower than that of SCC, to underline the greater importance of UVBs in the genesis of SCC (2). OCA is more severe in black even because it is considered a stigma, as if the child was born from the relationship with a white man or his ghost. Even more severe is the prejudice that attributes magical powers to parts of the body of the albino subject that has led to the massacre of hundreds of albino children in Africa (1).